Mitofusin 2 Dysfunction and Disease in Mice and Men - Dorn, Gerald W. (Frontiers in Physiology, 2020)
A causal relationship between Mitofusin (MFN) 2 gene mutations and the hereditary axonal neuropathy Charcot-Marie-Tooth disease type 2A (CMT2A) was described over 15 years ago. During the intervening period much has been learned about MFN2 functioning in mitochondrial fusion, calcium signaling, and quality control, and the consequences of these MFN2 activities on cell metabolism, fitness, and development. Nevertheless, the challenge of defining the central underlying mechanism(s) linking mitochondrial abnormalities to progressive dying-back of peripheral arm and leg nerves in CMT2A is largely unmet. Here, a different perspective of why, in humans, MFN2 dysfunction preferentially impacts peripheral nerves is provided based on recent insights into its role in determining whether individual mitochondria will be fusion-competent and retained within the cell, or are fusion-impaired, sequestered, and eliminated by mitophagy. Evidence for and against a regulatory role of mitofusins in mitochondrial transport is reviewed, nagging questions defined, and implications on mitochondrial fusion, quality control, and neuronal degeneration discussed. Finally, in the context of recently described mitofusin activating peptides and small molecules, an overview is provided of potential therapeutic applications for pharmacological enhancement of mitochondrial fusion and motility in CMT2A and other neurodegenerative conditions.